Simulation Analysis of the Influence Law of Belt Width on the Noise of Automotive Synchronous Belt - Li Zhanguo; Li Shuiqing; Shi Yaochen (Jixie chuandong)
Taking the ZA automotive synchronous belts that the belt width is 19 mm and 25 mm as research object,the influence of the belt width on the vibration and noise of the automotive synchronous belt is analyzed in theory. A finite element analysis model of the ZA automotive synchronous belt drive system is established,the natural frequency characteristic of the automobile synchronous belt transverse vibration and its harmonic response under the action of meshing impact excitation are analyzed,and taking the surface vibration displacement of the synchronous belt obtained by harmonic response analysis as boundary condition,the acoustic boundary element analysis model of the automobile synchronous belt is established by the direct boundary element method that its sound field is closed,the radiated noise of automotive synchronous belt is simulated and analyzed,the sound pressure cloud picture and the frequency response curve of radiation pressure of two synchronous belt with different bandwidth are obtained,and the influence law of the belt width on the vibration and noise of the synchronous belt is studied.